Detection and Blockchain-Based Collaborative Mitigation of Internet of Things Botnets. (20th April 2022) - Sajjad, Syed Muhammad; Mufti, Muhammad Rafiq; Yousaf, Muhammad; Aslam, Waqar; Alshahrani, Reem; Nemri, Nadhem; Afzal, Humaira; Khan, Muhammad Asghar; Chen, Chien-Ming
Abstract : DDoS (distributed denial of service) attacks have drastically effected the functioning of Internet-based services in recent years. Following the release of the Mirai botnet source code on GitHub, the scope of these exploitations has grown. The attackers have been able to construct and launch variations of the Mirai botnet thanks to the open-sourcing of the Mirai code. These variants make the signature-based detection of these attacks challenging. Moreover, DDoS attacks are typically detected and mitigated reactively, making DDoS mitigation solutions very expensive. This paper presents a proactive IoT botnet detection system that detects the anomalies in the behavior of the IoT device and mitigates the DDoS botnet exploitation at the source end, which makes our proposal a low-cost solution. Further, this paper uses a collaborative trust relationship-based threat intelligence-sharing mechanism to prevent other IoT devices from being compromised by the detected botnet. The researchers have evaluated the collaborative threat intelligence sharing mechanism using Ethereum Virtual Machine and Hyperledger. The performance of our proposed system can detect 97% of the Mirai botnet attack activities. Furthermore, our collaborative threat intelligence sharing mechanism based on the Ethereum Virtual Machine showed more scalability.